Language Learning and Early Literacy Building Capacity of Preschool Teachers - Soni, Romila (JOURNAL OF INDIAN EDUCATION, 2020)
A growing body of researches shows that teachers’ knowledge and skills required to handle young children early literacy is crucial for children’s smooth and successful transitions to primary school. The recent interventions under the study by the researcher entitled “Situational Analysis of DM schools and Designing of Model Preschools” in the four DM schools of NCERT provide additional insights about the significance of building capacity of teachers in language and emergent literacy. One of the prime objectives of this two-phased study was to design activity areas and promote early literacy in the preschools located at four Regional Institutes of Education (RIEs) of NCERT. The preschool personnel of four RIEs were also interviewed and the findings indicated that the preschool and early primary teachers lack the disciplinary knowledge required to promote early literacy at the preschool stage. The present paper looks at the importance of early literacy in today’s preschool education especially in the first five to six years of young children’s lives. It is a basic human right of every child to get early literacy experiences through playful activities and games. It also examines various ways of implementing joyful and interactive activities to develop children’s skills in early literacy across the preschool programme. The present paper focuses on how teachers’ capacity need to be strengthened because early literacy is crucial to future learning and language is the basis to learn other subjects. It also recommends for strengthening the early literacy component in the training programs designed for the preschool and grade one teachers.